Epidemiology of alcohol use in the general population of Togo. (December 2015) - Agoudavi, K.; Dalmay, F.; Legleyle, S.; Kumako, K.; Preux, P.M.; Clément, J.P.; Falissard, B.; Nubukpo, P.
Abstract: Introduction: Alcohol use is responsible for a high level of mortality and morbidity throughout the world. The WHO global strategy recommends that the detrimental effects of alcohol use be reduced. Aims: The objective of this paper was to investigate, using data from the 2010 Togo STEPS survey, alcohol use and other health-related factors in the general population of Togo. Methods: This epidemiological investigation using the STEPwise approach was undertaken from December 1st, 2010, to January 23rd, 2011, throughout the five regions of Togo. Togo is a low-income country (World Bank) located in West Africa. The study involved 4800 people aged 15 to 64 who were representative of the population of Togo and who were selected using the one-stage cluster sampling method. Results: The sample was young and predominantly male. Approximately one-third of the respondents were alcohol abstainers, with the majority of these being women. Approximately the same proportion of current drinkers (daily consumption) by gender was observed. The reported daily average consumption of alcohol was 13 g of pure alcohol for men and 9 g for women. The mean number of heavy drinking days over the previous 30 days was higher for men (3 days), and this included 37.5% of the men who drink. Conclusion: We suggest a comparative analysis of the prevalence of harmful alcohol use in Togo and the WHO African region. Highlights: Men consumed an average of 13 g of pure alcohol daily. Women consumed an average of 9 g of pure alcohol daily. A comparative analysis of the prevalence of harmful alcohol use in Togo vs the African region is recommended.